MicroRNA: sex steroids, hormonal carcinogenesis, hormonal sensitivity of tumor tissue - A. V. Malek; L. M. Bershtein (Успехи молекулярной онкологии, 2015)
Sex hormones, regulating normal physiological processes of most tissues and organs, are considered to be one of the key factors in the development and progression of the reproductive system cancer. Recently, the importance of the system for post-transcriptional control of gene expression mediated by short single-stranded RNA molecules (microRNA) became evident. This system is involved in regulation of normal physiological processes and in the pathogenesis of many diseases, including cancer. In review we discuss the relationship between the two regulatory systems – sex hormones and microRNAs. The relationship of these systems is considered in the context of two tumors – breast and prostate cancer. In particular, the history of research on the role of sex hormones in the pathogenesis of breast cancer and prostate cancer is briefly covered. Additionally, modern scientific data on the biogenesis and biological role of microRNAs are presented in more detail. In the cells of the hormone-sensitive tissues, sex hormones regulate the microRNA-mediated machinery of gene expression control by two known ways: specifically, affecting the activity of individual microRNA molecules and non-specifically by altering the efficiency of microRNA biogenesis and activity of RNA-induced silencing complex. This downstream regulatory network substantially enhances biological effects of sex hormones at physiological conditions. Malignant transformation leads to a distortion of the regulatory effects of sex hormones that crucially influence the system of microRNA-regulated post-transcriptional control of gene expression. The most established and clinically significant example of such phenomenon is the loss of sensitivity of cells to the regulatory action of these hormones. As a consequence, cancer cells acquire the ability to active proliferation without stimulation with sex hormones. This effect is partly mediated by microRNAs. Also, relevant experimental data indicating the involvement of microRNAs in the phenomenon of breast cancer and prostate cancer cells hormone resistance are discussed in the review.Conception of the possible primary role of microRNAs in the process of malignant transformation and distortion of hormonal regulation is based on a smaller number of scientific reports. In general, in accordance with the main biological role of microRNAs, latter may affect sex hormones function via interaction with the mRNAs of hormone receptors and inhibition of their synthesis. As a result, the effect of many microRNA is converging on the single mRNA, results in suppression of corresponding protein function and, in the end, leads to inhibition of regulatory cascade downstream of sex steroids.Finally, the analysis of the fundamental aspects of sex hormones – microRNA interplay is supplemented by brief overview of clinically significant problems. The prospects for development and introduction into clinical practice innovative methods of diagnosis, prediction and optimization of therapy of breast and prostate cancers are discussed as well.